2012
DOI: 10.1074/jbc.m112.420224
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Amyloid-β Endocytic Trafficking and Lysosomal Degradation by Apolipoprotein E Isoforms

Abstract: Background: Apolipoprotein E (apoE) regulates amyloid-␤ (A␤) clearance in an isoform-dependent manner. Results: Internalized A␤ traffics to lysosomal and recycling pathways. ApoE3 more efficiently promotes A␤ lysosomal trafficking and degradation than apoE4. Conclusion: ApoE isoforms differentially affect A␤ lysosomal trafficking and degradation. Significance: Differential effects of apoE isoforms on A␤ cellular degradation may explain why apoE4 is a risk factor for Alzheimer disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
141
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 155 publications
(157 citation statements)
references
References 45 publications
(40 reference statements)
9
141
1
2
Order By: Relevance
“…Previous results have shown that the detergent and guanidine extraction pattern of mouse apoE parallels that of A␤42 in 5ϫFAD mice (5), and the proportion of apoE/A␤ in insoluble fractions was increased in AD synaptosomes compared with controls. 6 Importantly, insoluble apoE4/A␤ complex may accumulate in autophagic structures within synaptic terminals (66,67). However, the effect of APOE genotype on soluble synaptic apoE/A␤ levels is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous results have shown that the detergent and guanidine extraction pattern of mouse apoE parallels that of A␤42 in 5ϫFAD mice (5), and the proportion of apoE/A␤ in insoluble fractions was increased in AD synaptosomes compared with controls. 6 Importantly, insoluble apoE4/A␤ complex may accumulate in autophagic structures within synaptic terminals (66,67). However, the effect of APOE genotype on soluble synaptic apoE/A␤ levels is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…ApoE and A␤ bind to each other and also to their common receptors, including LRP1, LDLR, and heparan sulfate proteoglycan (11,12). Thus, apoE might compete with A␤ for receptor binding (67), although if it forms complexes with A␤, it might also facilitate cellular A␤ binding and uptake (28). Thus, the specific effects of apoE on A␤ clearance may be depending on their concentrations, apoE isoforms, apoE lipidation status, A␤ aggregation status, and specific cell types.…”
Section: Discussionmentioning
confidence: 99%
“…After washing two times with PBS, cells were dissolved in 5 M guanidine in 50 mM Tris-HCl (pH 8.0). To measure A␤42, samples were captured with mAb 2.1.3 followed by detection with HRP-conjugated Ab5 (28).…”
Section: Methodsmentioning
confidence: 99%
“…Most internalized A␤ is delivered to the lysosomal pathway for degradation (32). We then studied whether synj1 reduction would affect the amount of Alexa Fig.…”
Section: Ps1⌬e9mentioning
confidence: 99%
“…These results suggest that internalized A␤ 42 is transported more rapidly to the endosome/lysosome degradation pathway in neurons with synj1 reduction. 2 Levels-Furthermore, to assess lysosomal degradation of A␤, we tested the effects of lysosomal inhibitors (leupeptin, pepstatin A, and E-64d), which block lysosomal enzyme activities (32,33). N2a cells transfected with synj1 or control siRNA for 4 days were then incubated in the presence or absence of lysosomal inhibitors for 24 h. The amount of media and cell-associated A␤ in the presence of lysosomal inhibitors, determined by IP/Western blotting, were significantly increased (Fig.…”
Section: Delivery Of Internalized A␤ 42 To Lamp1 ϩ Lysosomes Increasementioning
confidence: 99%